PERLINDUNGAN HUKUM KONSUMEN DALAM TRANSAKSI JUAL BELI PELIHARAAN REPTIL SCARA ONLINE DI SURAKARTA - Razzaq Atalarik; Asianto Nugroho; Sapto Hermawan (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2022)
This article aims to examine consumer legal protection, advantages and disadvantages in online buying and selling of reptiles in this increasingly sophisticated era of globalization which is a new lifestyle in transactions in Surakarta. The research method used is normative research, statutory approach, researching consumer protection regulations against online buying and selling, then processed and analyzed using legal interpretation and argumentation systematically and written descriptively. The results of research regarding the legal protection of consumers buying and selling reptiles online in Surakarta for consumers experiencing losses. In Law No. 19 of 2016 in Article 28 paragraph 1 regarding consumer losses in e-commerce, it is only a general rule. PP N0 71 of 2019, in principle, business actors can be held accountable, namely contractual, presumption of responsibility and absolute responsibility. The UUPK in Article 19 regulates the responsibility for compensation and traditional buying and selling transactions. The responsibility of business actors to buyers in buying and selling online has not been specifically regulated. so that the government as a regulator is very urgent to take action. reconstruction of Law Number 19 of 2016 concerning ITE and induced in the RUUPK process which is still in the Prolegnas process at the DPR RI. The advantages of buying and selling reptiles online are because of new lifestyles/trends, various ease of accessing internet applications, fast, practical transaction processes, saving time, energy and costs without having to visit the location and send it to the consumer's house. Weaknesses are prone to fraud, incompatibility of animals being sent, stressful conditions, running away, getting sick, dying at the time of delivery. If there is a default, the consumer has no clarity and legal certainty